Reading From the Crystal Ball: The Laws of Moore and Kurzweil Applied to Mass Spectrometry in Food Analysis - Rychlik, Michael; Schmitt-Kopplin, Philippe (Frontiers in Nutrition, 2020)
Predictions about the future knowledge of the complete food metabolome may be essayed based on the laws of Moore and Kurzweil, who foresee a technological development on exponential behavior. The application of these laws allows us to extrapolate and predict roughly when each single metabolite in foods could be (1) known, (2) detectable and (3) identifiable. From current metabolite data bases and their coverage over time the conservative number of all relevant food metabolites can be estimated to be 500,000, predicting them being known around 2025. Extrapolating the current developments in chromatography and mass spectrometry technology, the year 2032 can be estimated, when single molecule detection will be possible in “routine” mass spectrometry. A possible forecast for identification of all food metabolites, however is much more difficult and estimated at earliest in 2041 as the year, when this may be achieved. However, the real prediction uncertainty is extreme and is discussed in the essay presented here.